Special economic zones in the People's Republic of China - Petra Pissula; Dieter Lösch (Intereconomics, 1990)
By setting up a number of special economic zones, i.e. clearly demarcated regions regulated by special commercial legislation, the Chinese leadership intended, after a period of economic isolation, to integrate China more closely into the international division of labour and to stimulate production by using foreign capital and technology. Have the special economic zones so far been able to live up to expectations? What are the prospects for the future?
Keywords: 330